Removal of Mimosine from Leucaena leucocephala (Lam.) de Wit Seeds to Increase Their Benefits as Nutraceuticals - Wardatun, Sri; Harahap, Yahdiana; Mun'im, Abdul; Saputri, Fadlina Chany, Dr.; Sutandyo, Noorwati (UI Scholars Hub, 2020)
The Leucaena leucocephala (Lam.) de Wit tree contains pharmacologically active compounds and can easily be found in abundant quantities. The utilization of this tree as a source of nutraceuticals would increase its value. The extraction yields show the number of compounds that have been extracted by solvent. However, Leucaena leucocephala (Lam.) de Wit seeds also contain mimosine, which can cause hair loss. The present study investigated the process of removing mimosine from the seeds. Three treatments were applied to these seeds: treatment without soaking, soaking with distilled water for 24 hours, and splitting the seeds in half and then soaking with distilled water for 24 hours. The seeds were dried, ground, and then extracted with different concentrations of ethanol solvent. The mimosine levels of the extracts were measured with a JascoV-730 spectrophotometer using ferry chloride as a reagent. The results showed that the soaking process and the concentration of ethanol had significant effects on the extract yields and mimosine levels. The unsoaked seeds, extracted with 70% ethanol, produced the highest ratio of extract yield to mimosine level. Therefore, 70% ethanol can be used as a solvent to utilize unsoaked seeds as nutraceuticals.